98. Patient-specific estimation of the red marrow extracellular fluid fraction for improving the accuracy of red marrow dosimetry in radioimmunotherpy. (December 2018) - Pacilio, M.; Borrazzo, C.; Galea, N.; Basile, C.; Carbone, I.
Abstract : Purpose: The red marrow (RM) is the dose-limiting organ in radioimmunotherapy. The RM dosimetry is usually calculated by radioactivity concentrations of blood samples: RM kinetics is derived multiplying the blood kinetics by the "red marrow-to-blood activity concentration ratio" (RMBLR), calculated by patient-specific RM extracellular fluid fraction (RMECFF) and hematocrit (HCT) i.e., RMBLR = RMECFF/(1-HCT)[1] . Preliminarily, the possible use of Contrast-Enhanced Magnetic Resonance Imaging (CEMRI) for estimating the patient-specific RMECFF was here investigated. Methods: 9 patients (5 men, 4 women) studied with CEMRI for cardiac disorders were examined. Pre- and post-contrast T1 mapping by MOLLI (modified Look-Locker inversion-recovery) sequences was performed, and the extracellular volume fraction (ECV) map was calculated by a novel method - based on a Fast Non-linear Least Squares (FNLS) algorithm. The mean ECV of the spongiosa volume (SV) inside the dorsal vertebra at the heart level was obtained as mean value in a region-of-interest (ROI) lying wholly within the SV. Results: The mean ECV of the SV was (mean[range]): 29.9[24.0–35.3]%. Considering the ECV as a preliminary estimation of the RMECFF, and accounting also for the patient HCT values (ranging from 0.340 up to 0.499), the mean RMBLR was 0.430[0.316–0.546], in a good agreement with the range of 0.2–0.4 generally reported in the literature (even though values sometimes well outside this range were also observed)[1] . Conclusion: The CEMRI is accurate and very promising for patient-specific RMECFF estimations. Accuracy improvements by MOLLI sequence optimisation, or correction for the presence of trabecular bone and fatty tissue into the SV, are currently under investigation.